Chronostratigraphy of uplifted Quaternary hemipelagic deposits from the Dodecanese island of Rhodes (Greece). Issue 1 (July 2016) - Quillévéré, Frédéric; Cornée, Jean-Jacques; Moissette, Pierre; Lopez-Otalvaro, Gatsby Emperatriz; Baak, Christiaan van; Münch, Philippe; Melinte-Dobrinescu, Mihaela Carmen; Krijgsman, Wout
Abstract: An integrated magneto-biostratigraphic study, based on calcareous nannofossils and foraminifers, together with the radiometric dating of a volcaniclastic layer found in several outcrops, was carried out on the hemipelagic deposits of the Lindos Bay Formation (LBF) at six localities on the island of Rhodes (Greece). Our highly refined chronostratigraphic framework indicates that the lower and upper lithos-tratigraphic boundaries of the LBF are diachronous. Associated with the 40 Ar/ 39 Ar age determination of 1.85 ± 0.08 Ma for the volcaniclastic layer, our data show that among the investigated outcrops, the Lindos Bay type locality section provides the longest record (1.1 Ma) of the LBF. Hemipelagic deposition occurred continuously from the late Gelasian ( 1.9 Ma) to the late Calabrian ( 0.8 Ma), i.e., from Chrons C2n (Olduvai) to C1r.1r (Matuyama) and from nannofossil Zones CNPL7 to CNPL10. This long record, together with the hemipelagic nature of the deposits, make the Lindos Bay type locality section a unique element in the eastern Mediterranean region, allowing future comparisons with other early Quaternary deep-sea sections available in the central and western Mediterranean regions.